A national survey amongst UK otolaryngologists regarding the treatment of Ménière’s disease - Smith, W K; Sankar, V; Pfleiderer, A G (Journal of laryngology and otology, 2005)
Since Dr Prosper Ménière described the vertiginous syndrome that now bears his name, a large variety of medical and surgical treatments have been introduced. To determine the way in which this condition is currently managed in the United Kingdom, a postal survey amongst consultant otolaryngologists was carried out. It revealed that 52 per cent were actively involved in the treatment of patients with Ménières disease using a wide range of medical and surgical therapies that have little or no evidence base. The survey found that 94 per cent of surgeons prescribe betahistine, 63 per cent diuretics and 71 per cent advise salt restriction to their patients, while 52 per cent of surgeons continue to recommend saccus decompression and 50 per cent are still inserting a grommet. However, two thirds of respondents now advocate the use of gentamicin therapy despite it only being introduced to this country just over 10 years ago. The results of this study and their relevance to the recommended present day management of Ménière’s disease are discussed.